LINE-1 DNA methylation and congenital heart defects in Down syndrome - Vraneković, Jadranka (Array, 2019)
DNA methylation is a key epigenetic mechanism that plays a significant role in regulating gene activity during cardiac development. Congenital heart defects (CHD) are one of the most common abnormalities occurring in 40% -60% of cases with Down syndrome (DS). The main aim of this study was to establish the association of long interspersed nucleotide element-1 (LINE-1) DNA methylation in children with DS and the presence of CHD. The LINE-1 DNA methylation was investigated in peripheral blood lymphocytes on a sample of 42 people with DS by quantification of LINE-1 methylation using the MethyLight method. No significant differences in global DNA methylation were found according to the presence of CHD (P=1.000), but values of LINE-1 DNA methylation were significantly influenced by gender (R2=19.1%; P=0.025). Significant probability of 19.1% was found in women with DS who had lower LINE-1 DNA methylation values than DS male . Gender was a statistically significant predictor of LINE-1 DNA methylation, although the difference was not statistically significant, female subjects had lower LINE-1 DNA methylation values (P=0.068). Further research will clarify the role of lower LINE-1 DNA methylation in the formation of CHD among DS females.